2020
DOI: 10.1002/jsfa.10845
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of green‐pea adulteration in pistachio nuts using Raman spectroscopy and chemometrics

Abstract: BACKGROUND Ground pistachio nut is prone to adulteration because of its high economic value and wide usage. Green pea is known as the main adulterant in frauds involving pistachio nuts. The present study developed a new, rapid, reliable and low‐cost methodology by using a portable Raman spectrometer in combination with chemometrics for the detection of green pea in pistachio nuts. RESULTS Three different methods of Raman spectroscopy‐based chemometrics analysis were developed for the determination of green‐pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Previous Data from several studies reported that the 4000-600 cm −1 spectral range included fingerprinting spectral information, which could be used to obtain classification patterns of authentic and counterfeit herbal samples [21]. HCA is an algorithmic approach and it provides an opportunity to observe the classification pattern of authentic and adulterated samples on 2-D dendrogram plots [22]. Dendrograms are composed of branches which include sample sets and sub-sets.…”
Section: Spectral Properties Of Mentha Piperita Essential Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous Data from several studies reported that the 4000-600 cm −1 spectral range included fingerprinting spectral information, which could be used to obtain classification patterns of authentic and counterfeit herbal samples [21]. HCA is an algorithmic approach and it provides an opportunity to observe the classification pattern of authentic and adulterated samples on 2-D dendrogram plots [22]. Dendrograms are composed of branches which include sample sets and sub-sets.…”
Section: Spectral Properties Of Mentha Piperita Essential Oilmentioning
confidence: 99%
“…The current research used two different multivariate calibration models (PLSR and PCR) for the prediction of Mentha spicata and L-menthol contents of adulterated Menhta piperita samples. These powerful chemometrics are widely used to detect and quantify suspicious additives or adulterants in the various matrices such as foods, beverages, and essential oil for the sustainability of originality of high-valued products [22]. In the present study, research calibration and cross-validation was carried out for the samples of Mentha piperita EO (MP1, MP2, MP3), Mentha spicata EO (MS1, MS2, MS3), L-menthol (LM1, LM2, LM3) and adulterated Mentha piperita EOs at the concentration levels of 0, 1, 2, 4, 8, 16, 32, 64, 100% (v/v).…”
Section: Prediction Of Mentha Spicata and L-menthol Contents Of Adulterated Mentha Piperita Samplesmentioning
confidence: 99%
“…Chemometric analyses of nuts described in the literature are primarily related to data on the chromatographic fingerprint [ 61 ], interpretation of results obtained by Raman spectroscopy [ 62 ] or Fourier transform infrared spectroscopy [ 63 ], or a combination of chemometric and metabolomic techniques [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides adulteration causing image loss of food products due to dishonesty and depriving consumers of vital nutrients, adulterants can be hazardous to human health as they may be toxic or induce allergies [77]. Examples of adulterations that can be detected by Raman spectroscopic methods include olive oil adulterated with rapeseed and corn oil [78], honey adulterated with fructose, glucose, inverted sugar, hydrolyzed inulin syrup, and malt must [79], pistachio nuts adulterated with green peas [80], cassava starch adulterated with wheat flour or sodium bicarbonate [77], and butter adulterated with margarine [81].…”
Section: Detection Of Additives and Adulterationmentioning
confidence: 99%